The relationship of lens thickness and anterior chamber depth with intraocular pressure during hemodialysis - Wai Seng, Chiang (2011)
Introduction: Hemodialysis is a common renal replacement therapy in the end stage renal failure. Fluctuation of intraocular pressure occurred during hemodialysis. Individuals with compromised aqueous outflow facility have increased risk of symptomatic elevation of intraocular pressure. Lens thickness changes may result in alteration of anterior chamber depth that can further compromise aqueous drainage. Early detection of the lens thickness changes during hemodialysis can prevent elevation of intraocular pressure and visual loss. Thus, evaluation of the lens thickness and anterior chamber depth with intraocular pressure changes during hemodialysis are essential. Objectives: To determine the mean lens thickness and the relationship between lens thickness and anterior chamber depth, between anterior chamber depth and intraocular pressure as well as between lens thickness and intraocular pressure during hemodialysis. Methodology: 70 eyes from 70 study subjects were recruited from Hemodialysis Unit, Queen Elizabeth Hospital. Lens thickness, anterior chamber depth and intraocular pressure were measured at 0hour, 2hour and 4hour of hemodialysis. The mean lens thickness, anterior chamber depth and intraocular pressure changes based on time effect of hemodialysis were analyzed with repeated measures ANCOVA and multiple paired samples T-test with bonferonni correction (p=0.017). The relationship between study variables were evaluated with correlation analysis. Results: There were significant increased mean lens thickness and intraocular pressure among all study subjects by 0.21 ± 0.69 mm (p=0.015) and 1.26 ± 3.02mmHg (p=0.001) in the first 2hours of hemodialysis. The anterior chamber depth changes was insignificant. The mean lens thickness and intraocular pressure were increased more in diabetic and older age group in the first 2hours of hemodialysis but significant for intraocular pressure changes only. At 2hours of hemodialysis, there were inverse correlation between lens thickness and anterior chamber depth, inverse correlation between anterior chamber and intraocular pressure, and linear correlation between lens thickness and intraocular pressure but not significant. At 4hour of hemodialysis, there was a significant fair inverse correlation between lens thickness and anterior chamber depth (r = -0.286, p=0.016) but the correlation between other variables were not significant. Conclusions: In the first 2hours of hemodialysis, there were significant increased mean lens thickness and intraocular pressure but no significant correlation between study variables suggested other mechanisms of raised intraocular pressure were involved rather than due to lens thickness changes only. A significant inverse relationship between lens thickness and anterior chamber depth was established at 4hours of hemodialysis but it didn’t lead to significant raised intraocular pressure in normal eyes. Intraocular pressure rise may become significant if individuals have compromised aqueous drainage. Diabetes mellitus and age had significant influence on intraocular pressure but not on lens thickness and anterior chamber depth during hemodialysis.